1993
DOI: 10.1111/j.1399-6576.1993.tb03709.x
|View full text |Cite
|
Sign up to set email alerts
|

Beclomethasone prevents postoperative sore throat

Abstract: The effects of a dose of beclomethasone inhaler (50 micrograms) or lidocaine 10% spray on postoperative sore throat were studied in 120 patients undergoing tracheal intubation for elective surgical procedures. Fifty-four patients (90%) in the beclomethasone group scored no postoperative sore throat compared with 27 (45%) in the lidocaine group (P < 0.001). Beclomethasone inhaler seems to be highly effective in the prevention of postoperative sore throat and is therefore to be recommended before tracheal intuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 19 publications
3
31
0
2
Order By: Relevance
“…This was supported by one study [8]. But many studies did not agree with this finding [6,7,11,12,[17][18][19][20]. In our IJBR (2015) 6 (07) www.ssjournals.com study the maximum duration of anaesthesia was 758 minutes.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This was supported by one study [8]. But many studies did not agree with this finding [6,7,11,12,[17][18][19][20]. In our IJBR (2015) 6 (07) www.ssjournals.com study the maximum duration of anaesthesia was 758 minutes.…”
Section: Discussionsupporting
confidence: 64%
“…Smokers tend to have hyper reactive airway and they are more prone to have respiratory complications in the intraoperative and post operative period. Though many studies [6,13,18] did not find any correlation between smoking and postoperative sore throat, our study showed smoking as a significant predisposing factor for the development of postoperative sore throat. In our study 48% of smokers had sore throat whereas only 27.3% of nonsmokers had sore throat.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations